Advertising and promotion : an integrated marketing communications perspective / George E. Belch, Michael A. Belch - Belch, George E.
To effectively plan, implement, and evaluate Integrated Marketing Communications (IMC) programs, one must understand the overall marketing process, consumer behavior, and communications theory. Belch/Belch's Advertising and Promotion: An Integrated Marketing Communications Perspective draws from the authors’ extensive research in advertising, consumer behavior, communications, marketing, sales promotion, and other fields to give students a basis for understanding the marketing communications process, how it influences consumer decision making, and how to develop promotional strategies. In addition to thorough coverage of advertising, Belch's eleventh edition has chapters on sales promotion, direct marketing, the Internet including social media and mobile marketing, support media such as outdoor advertising, product placement and integration, and publicity/public relations, with emphasis on the integration of advertising with other promotional-mix elements and the need to understand their role and overall contribution